US AND CHINA EXPERIENCE IN ENSURING CYBERSECURITY AND THEIR FEATURES (American Journal of Technology and Applied Sciences, 2024)
The essence of cybersecurity as a social phenomenon is the state and quality of the actual social relations in society that provide the necessary level of guarantees for its security, and allow the state to predict, promptly identify, prevent and eliminate real and potential dangers and threats to national interests.